Develop a regression model for relationship between psychophysical and biomechanics factors of push activities - Mohd Ghazali, Athirah (2016)
In aerospace industries , many working tasks required their workers to perform the works in push-pull activity.The workers need to push or pull the mould tool in a long distance into a workplace.Performing these activity continuously throughout the working hours,may lead to an early initiation of musculoskeletal disorders (MSDS)symptoms as workers developed muscle fatigue particularly at hand muscle.Grip strength on the other hand is the force applied by the hand to push objects and is a part of hand strength.Repetitive usage of hands will create an imbalance between closing and opening(antagonist)muscles, which can lead to problem such as carpal tunnel syndrome (CTS).The primary purpose of this study is to develop regression model based on psychophysical and biomechanical factors that contributes to fatigue,in which the models can predict the relationship between the input parameters and output responses.Regression analysis is used as it is easy,user-friendly and cost-effective method to develop a model.The methodology used for this study focuses on three types of data collection which are; questionnaire and observation which conducted as the preliminary study to prove the problems that have been stated and experimental is conducted by using surface Electromyography (sEMG)and Tekscan system to evaluate the muscle fatigue and hand grip pressure force of the Lay-up workers who are performing push activity.This study investigate the hand grip pressure force for the right hand and left hand within 5 minutes and I0 minutes of time exposure while workers pushing the mould tool,and study the relationship between time exposure with hand grip pressure force and muscle fatigue.The input parameters evaluated are time exposure,hand side and body mass index (BMI);while the output responses are muscle fatigue (voltage),hand grip pressure force (left hand),and hand grip pressure force (right hand).Two polynomial equations are successfully developed and validated.The modelling validation runs are within 90% prediction interval of the developed models and their residual errors compared to the predicted values are le s than 10%. The significant parameters that influenced the output responses are also identified.Muscle fatigue are influenced by time exposure,hand side,BMI,and interaction between hand side and BMI;while hand grip pressure force are infuenced by time exposure,hand side,BMI, and interaction beetween time exposure and hand side,interaction between time expossure and BMI. and interaction between hand side and BMI.